The Relationship of Faith and Tolerance in The Film One Amen Two Faith: Living Qur'an Perspective - Husna, Rifqatul; Zayyadi, Ach; Wirendri, Dwiki Oktafiana (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This paper aims to analyze the relationship between faith and tolerance in the film One Amen Two Faith, an example that the relationship between religion and tolerance plays a vital role in this millennial era, by using qualitative research methods that describe in-depth by watching the film by analyzing the sources which will later be analyzed by studying the living Qur'an. The results of the research on the film one amen, two faiths present the closeness of the relationship between religion and tolerance; several thoughts describe mutual respect, respect, and unity in differences, especially differences in beliefs, so that a series of things can be contemplated and learned from. This research implies the importance of implementing Islamic values in interacting with fellow human beings who have different religious, social, and cultural backgrounds to create benefits for all.